Konsep Al-baiyyinah dan Implkasinya Terhadap Amal Perbuatan Manusia (Qs Al-Baiyyinah ayat 1-8) serta Zihar dalam Qs Al-mujadillah ayat 1-4 Perspektif Tafsir Maqasid: onsep Al-baiyyinah dan Implkasinya Terhadap Amal Perbuatan Manusia (Qs Al-Baiyyinah ayat 1-8) serta Zihar dalam Qs Al-mujadillah ayat 1-4 Perspektif Tafsir Maqasid - Siti Farida; Mohammad Thoyyib Madani; Rifki Rufaida (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
Abstract This study aims to analyze the concept of Al-Bayyinah in QS. Al-Bayyinah [98]: 1-8 and the concept of Zihar in QS. Al-Mujadilah [58]: 1-4, as well as to explore their implications for the dynamics of human actions through the lens of Maqashid Tafsir (the objectives of Islamic law). This study is a qualitative library research employing a descriptive-analytical method based on intertextual approaches to both classical and contemporary exegesis (tafsir) books. The results demonstrate that from the perspective of Maqashid al-Shariah, QS. Al-Bayyinah centers on Hifzh ad-Din (preservation of religion) and Hifzh al-’Aql (preservation of intellect) by emphasizing that all righteous deeds must be rooted in clear evidence (bayyinah) and sincerity to attain Allah's pleasure. Meanwhile, QS. Al-Mujadilah verses 1-4 reforms the pre-Islamic Jahiliyyah tradition of zihar as a manifestation of Hifzh an-Nasl (preservation of lineage/family) and Hifzh an-Nafs (preservation of soul/honor) to protect women's rights within the marital institution. This study concludes that both concepts imply the necessity of reconstructing human deeds, both in the theological-spiritual realm (sincerity in action) and the socio-domestic domain (linguistic accountability and kaffarah sanctions), to foster just well-being (maslahah) in this world and the hereafter. Keywords: Al-Bayyinah, Zihar, Human Actions, Maqashid Tafsir, Maslahah.